FLEXIBILITY OF HINDUISM IN A SOJOURNING LAND STUDY ON DIASPORIC BALINESE HINDU IN CIMAHI, WEST JAVA PROVINCE OF INDONESIA - Zaenal Abidin Eko Putro; Kustini Kustini (Analisa: Journal of Social Science and Religion, 2017)
In so far, articles portraying Balinese Hindu who settles in far away from Bali Island are less widely published. In recent development of Hinduism in Indonesia, Hindus community shows a dynamic process and tries to adapt culture of majority people in some areas. This article tries to explore the dynamics of Balinese Hindu community which is assumed a diasporic Balinese who settle in a small town Cimahi, West Java Province of Indonesia. This article shows that the Balinese Hindu in Cimahi can perform flexibility of Hindu doctrine as well as Hindu ritual which mean they do not totally follow the core of its culture, that is Balinese culture. Yet, they maintain banjar system and adhere Parisada Hindu Dharma of Indonesia’ decrees instead of joining India Hinduism of sampradaya. This article is stemmed from a qualitative research toward Hindu community in Cimahi of West Java province whereby they maintain their religious tradition (including pancayadnya) embedded with an old temple namely the Great Wira Loka Natha temple. This temple is regarded by themselves as the oldest Balinese temple in West Java which was built in 1978. To collect the data, the research uses observation, in-depth interview, focus group discussion as well as literature study.